Recovery of putative pathogens from paper point sampling at different depths of periodontal lesions - Nikola Angelov; Raydolfo M Aprecio; James Kettering; Tord Lundgren; Matt Riggs; Jan Egelberg (Dove Medical Press, 2009)
Nikola Angelov1, Raydolfo M Aprecio1, James Kettering1, Tord Lundgren2, Matt Riggs3, Jan Egelberg11School of Dentistry, Loma Linda University, Loma Linda, CA, USA; 2Department of Periodontology, University of Florida, Gainesville, FL, USA; 3Department of Psychology, California State University, San Bernardino, CA, USABackground: The aim of this study was to compare the recovery of three putative periodontal pathogens from periodontal lesions in samples using paper points inserted to different depths of the lesions.Methods: Twenty 6–8 mm deep periodontal lesions with bleeding on probing were studied. Microbial samples were obtained using paper points inserted to three different depths of the lesions: orifice of lesion; 2 mm into the lesion; and to the base of lesion. Culturing was used for recovery and identification of Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, and Prevotella intermedia.Results: The recovery of each of the three putative periodontal pathogens was similar following sampling at the various depths of the lesions.Conclusions: The findings may be explained by the fact that the paper points become saturated as they pass through the orifice of the lesion. Absorption of microorganisms will therefore primarily occur at the orifice. It is also conceivable that the pathogens may be present in similar proportions throughout the various depths of the periodontal lesions.Keywords: paper point sampling, P. gingivalis, P. intermedia, A. actinomycetemcomitans